Modern technologies for training economists-managers - Cherepanova, V. A.; Pererva, P. G. (ФОП Панов А. М., 2023)
The key directions of the formation of modern educational technologies are directly related to the progress and harmonization of education, as well as aimed at the self-realization of the individual. Information technologies are based on formation processes economic knowledge and productive thinking. In the innovative teaching of economic disciplines, the leading role is assigned to teaching aids, when the teacher does not just teach students, but performs the functions of stimulating educational activities among students and coordinates them.
Сучасні технології підготовки економістів-менеджерів
Keywords: higher education; universities; economist-manager; learning technologies